Some Hitting Leg Anthropometric Measurements and Its Relationship With Scoring From standing and Moving Positions - Majeed, Omer (Journal of Physical Education, 2018)
Some Hitting Leg Anthropometric Measurements and Its Relationship With Scoring From standing and Moving Positions The researcher aimed at identifying the values of some anthropometric measurement of the hitting leg and scoring skill from standing and moving positions as well as identifying the relationship between these measures and scoring skills from standing and moving positions. The researchers used the experimental method and the subjects were (16) players from Arbil club season 2018. The researcher designed a questioner that he distributed in the experts in soccer. The data was collected and treated using proper statistical operations to conclude that there is a positive statistical relationship between leg length, thigh girth and length and foot length in scoring from standing and moving positions in advance soccer players from Arbil club. Finally the researcher recommended using players with long legs for scoring from standing and moving positions.